A study of collective psychological ownership predicted by work environment and mediating role of employee self-efficacy among nursing staff in Oman. (13th January 2023) - Tahir, Muhammad
The coronavirus pandemic has highlighted the importance of healthcare staff and as a result, there is renewed interest in the management of healthcare staff. One concept which can perform a central role in managing healthcare staff is psychological ownership which is investigated in the current study. The study is based on three literature gaps including foci of psychological ownership, its measurement level, and the process approach of understanding antecedents of psychological ownership. Based on these literature gaps, the objectives of the study were to measure the effects of the work environment on nursing staff collective-psychological ownership and test the mediating role of self-efficacy. Data was collected through a survey from nursing teams from selected private hospitals in the Sultanate of Oman. The result indicates that work environment dimensions have a significant influence on nursing staff collective-psychological ownership. Additionally, we found support for self-efficacy as a mediator in this relationship.